Surgical findings & audiological outcomes of Stapedotomy in patients with Otosclerosis (Bangladesh Journal of Otorhinolaryngology, 2015)
Objective: This study was focused on the assessment of patients improvement in hearing, as measured by pure tone audiometry after stapedotomy for primary otosclerosis. Materials and Methods: This prospective clinical study was performed in a total of 50 patients diagnosed with Primary Otosclerosis, who underwent Stapedotomy at the Department of ENT & Head-Neck Surgery, Combined Military Hospital, Dhaka between June 2012 to January 2014. All patients were evaluated as per the candidacy criteria for stapedotomy and selected patients underwent surgery during the study period and were followed up for a period of 12 months in the Otology clinic. Pre-operative and Post-operative audiometric evaluation was done using conventional pure tone audiometry with standard calibrations. Post-operative audiometry was performed at 03 month, 06 months and 12 months. The bone-conduction & air conduction thresholds and the Air- Bone gap (ABG), were documented and analysed at 0.5 KHz, 1 KHz, 2 KHz and 4 KHz frequencies respectively. The subjective outcomes in hearing were also recorded with a patient satisfaction questionnaire to assess improvement in quality of hearing after stapedotomy. Results: Overall, the frequency specific pre-operative mean averaged Air Conduction thresholds were 63.3dB at 500Hz, 57.5dB at 1 KHz, 55.1dB at 2 KHz and 45.7dB at 4 KHz. The frequency specific post-operative mean averaged Air conduction thresolds were 34.6 dB at 500Hz, 28.9 dB at 1Kz, 30.5dB at 2Kz and 33.3dB at 4Kz.The frequency specific mean average post operative Air Bone Gap (ABG) closure was achieved by 28.7dB at 500Hz, 27.6 dB at 1KHz, 24.6 dB at 2KHz and 12.4 dB at 4KHz by the time of completion of the study at 01 year. A successful closure of AB gap to less than 10dB was achieved in the speech frequencies of 2 KHz and 4 KHz in 84% of cases. Overall, the frequency specific bone-conduction thresholds were unchanged postoperatively in all cases except one, showing that no significant sensori-neural impairment had occured due to the stapedotomy procedure. 1 patient developed post-op severe vertigo which was self-limiting after six weeks. A few interesting cases with anomalous intra-operative findings were also documented and reported herewith. These included monopodal stapes (n=1), anomolous facial nerve (n=1), laterally placed chorda tympani nerve (n=1), high jugular bulb, Malleus ankylosis (n=1) and persistent stapedial artery (n=1). All patients included in our study had significant subjective audiological improvement and responded satisfactorily to the questionnaire formulated to assess their hearing quality after stapedotomy. Conclusions: Our case study confirms that stapedotomy is a safe and successful procedure providing long-term hearing improvement in primary otosclerosis. Obliterative otosclerosis, biscuit or floating footplate, monopodal stapes, anomalous facial nerve and persistent stapedial artery may be special scenarios encountered during stapedotomy and they need judicious management by an experienced surgeon. Our study shows that meticulous selection of cases for stapedotomy will result in highly successful audiological outcomes. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22024 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 87-92